EFFECT OF DIFFERENT SEMEN EXTENDERS ON CAT EPIDIDYMAL SEMEN CRYOPRESERVATION - Acisu, Tutku Can; Akarsu, Serkan Ali; Polat, Eren; Baykalir, Yasin; Otlu, Onder; Cihangirogluf, Aslihan Cakir; Unsaldi, Emine (Cryo Letters, 2024)
BACKGROUND: Cryopreservation of spermatozoa is a biotechnology used for fertilization purposes and preservation of genetic material in various domestic species. OBJECTIVE: To determine the efficacy of two different commercial semen diluents in the cryopreservation of epididymal semen of domestic cats. MATERIALS AND METHODS: Twenty male cats aged between 1 - 3 years and weighing 2.5 - 4.5 kg were used in the study. The testicular tissues removed from the cats were immediately brought to the laboratory in physiological saline and the epididymal parts were trimmed in commercial semen extenders (INRA 96, Group I; OPTIXCELL, Group II). Diluted semen samples were cooled to 4 degrees C and filled into 0.25 mL straws. Semen samples were frozen in a programmable semen freezing device and then placed in a liquid nitrogen container at -196 C. Semen samples were thawed at 38 degrees C for 25 s. Thawed semen samples were evaluated in terms of motility and kinematic parameters using CASA. RESULTS: No statistical difference was found between the groups in terms of total motility, progressive motility, and velocity parameters at 4 degrees C. The rate of spermatozoa at slow speeds was found to be lower in group II. In addition, after freezing and thawing process, no statistical difference was observed between the groups in terms of motility, kinematics, and velocity parameters. CONCLUSION: Both commercial semen extenders can be used for cryopreservation of cat epididymal
Keywords: cat; cryopreservation; epididymis; semen extender; sperm.